2021
DOI: 10.3390/nu13030822
|View full text |Cite
|
Sign up to set email alerts
|

‘An Apple a Day’?: Psychiatrists, Psychologists and Psychotherapists Report Poor Literacy for Nutritional Medicine: International Survey Spanning 52 Countries

Abstract: Nutritional interventions have beneficial effects on certain psychiatric disorder symptomatology and common physical health comorbidities. However, studies evaluating nutritional literacy in mental health professionals (MHP) are scarce. This study aimed to assess the across 52 countries. Surveys were distributed via colleagues and professional societies. Data were collected regarding self-reported general nutrition knowledge, nutrition education, learning opportunities, and the tendency to recommend food suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 132 publications
2
19
0
3
Order By: Relevance
“…One of the major challenges of Nutritional Psychiatry Research is to gradually change the prevalent mindset shared by a majority of researchers and practitioners that psychiatric disorders are diseases of the brain, and do not involve the gut and its microbiome. An education of mental health professionals about the crucial role of diet and its effect on brain gut microbiome interactions, and the need for and interdisciplinary approach to this field is necessary to make progress in this area of psychiatry [ 136 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the major challenges of Nutritional Psychiatry Research is to gradually change the prevalent mindset shared by a majority of researchers and practitioners that psychiatric disorders are diseases of the brain, and do not involve the gut and its microbiome. An education of mental health professionals about the crucial role of diet and its effect on brain gut microbiome interactions, and the need for and interdisciplinary approach to this field is necessary to make progress in this area of psychiatry [ 136 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that passive dissemination strategies, such as printed educational materials, are more likely to change clinician behaviour when there is existing motivation [ 39 ]. In response to a recent survey of mental health professionals from 52 countries, 92% of respondents indicated that they were interested in expanding their knowledge of nutrition as a therapeutic approach to mental health care [ 21 ]. This high level of motivation suggests that the dissemination strategy is appropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Occupational therapists could support patients in making dietary changes by working in a behavioural activation, cognitive adaptation, or goal-setting framework. Overall, mental health professionals, such as our study population - psychiatrists, are well-trained in supporting behaviour change but nutritional training is lacking [ 21 ]. Future work with other mental health care providers to introduce, modify, or implement the tool may be valuable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One potential reason is diagnostic overshadowing, "a process by which physical symptoms are misattributed to mental illness" [20]. In addition, psychiatrists and mental-health teams are insufficiently aware of the somatic comorbidities and metabolic monitoring procedures for their patients with psychiatric disorders [21,22], and they have little to no training in nutrition [22]. This leads to a lower use of general preventive-care services and of routine specialized somatic care in people with an SMI, as compared to the general population [23].…”
Section: Introductionmentioning
confidence: 99%